INITIALISMS AS ENGLISH LEGAL ABBREVIATIONS (Scientific journal of the Fergana State University, 2023)
This study is devoted to the analysis of the ways of formation and identification of structural and functional features as well as graphics of English legal abbreviated terms - initialisms. Difficulties arise when a non-lawyer comes across legal initialisms, especially when there are synonyms, homonyms or polysemous as abbreviated units. The study of this problem leads to the need of considering the ways and methods of the formation of initialisms such as single-component abbreviations, multi-component abbreviations, acronyms, mixed type initialisms, their spelling and pronunciation. Examples of different types of legal initialisms according to the structure, spelling and pronunciation are provided.